A Vanadium‐Based Fluoroxide Cathode Material for Lithium‐Ion Storage with High Energy Density. (1st May 2022) - He, Xiaolong; Yan, Qi; He, Haiyan; Shang, Jian; Zhou, Xiaolong; Chanlek, Narong; Tunmee, Sarayut; Kidkhunthod, Pinit; Yao, Wenjiao; Tang, Yongbing
Abstract: High‐performance lithium‐ion batteries (LIBs) are required for the rising energy storage demand, while their development depends mainly on cathode materials. Vanadium‐based compounds are considered to be promising due to the feasibility of multielectron reactions arising from the rich valence states of vanadium (+2 to +5). Herein, for the first time the electrochemical properties of a vanadium‐based fluoroxide, β‐KVOF3, as a cathode for LIBs, are reported. After optimization, a reversible capacity as high as 274 mAh g −1, a stable 300 cycles lifetime, and an energy density comparable to LiFePO4 (650 vs 550 Wh kg −1 ) are achieved. Experiments and simulation study of reaction mechanism illustrate that such performance originates from the reversible V 3+ /V 5+ redox reaction, high structural stability of β‐KVOF3, and the pseudocapacitive process during charging and discharging. This study reveals that β‐KVOF3 is a promising cathode for Li‐ion storage and provides a new design idea for developing high‐performance LIBs cathode materials. Abstract : Based on the structural analysis and preliminary calculation, β‐KVOF3 is developed as a promising cathode material for lithium‐ion storage with high reversible capacity, high energy density, and good stability, and its reaction mechanism is unambiguously revealed by X‐ray photoelectron spectroscopy, synchrotron X‐ray absorption spectroscopy, etc.